Learning from the experts: enabling and studying DIY development of location-based visitor experiences - Bedwell, Benjamin D.; Slack, Peter; Greenhalgh, Chris (ACM, 2015)
In this paper we show how -- with the aid of enabling technology -- creative Location Based Experiences can be developed for visitors by non-technical professionals from the cultural heritage sector. We look at how these "Place Experts" approach and adopt web technologies to create and publish experiences including the roles they take on, the processes they adopt, and the way they appropriate the technology. We describe our short and long-term research engagements with the cultural heritage sector over the last three years and introduce Wander Anywhere, the website developed to enable this research. We find that place experts typically follow a four stage process in their engagement with location-based experiences, moving from comprehension to translation, development and finally approval. We suggest implications for the processes and technologies that might be employed by others seeking to support a similar type of engagement.